Delayed versus early initiation of renal replacement therapy for severe acute kidney injury: a systematic review and individual patient data meta-analysis of randomised clinical trials. Issue 10235 (9th May 2020) - Gaudry, Stéphane; Hajage, David; Benichou, Nicolas; Chaïbi, Khalil; Barbar, Saber; Zarbock, Alexander; Lumlertgul, Nuttha; Wald, Ron; Bagshaw, Sean M; Srisawat, Nattachai; Combes, Alain; Geri, Guillaume; et al.
Summary: Background: The timing of renal replacement therapy (RRT) for severe acute kidney injury is highly debated when no life-threatening complications are present. We assessed whether a strategy of delayed versus early RRT initiation affects 28-day survival in critically ill adults with severe acute kidney injury. Methods: In this systematic review and individual patient data meta-analysis, we searched MEDLINE (via PubMed), Embase, and the Cochrane Central Register of Controlled Trials for randomised trials published from April 1, 2008, to Dec 20, 2019, that compared delayed and early RRT initiation strategies in patients with severe acute kidney injury. Trials were eligible for inclusion if they included critically ill patients aged 18 years or older with acute kidney injury (defined as a Kidney Disease: Improving Global Outcomes [KDIGO] acute kidney injury stage 2 or 3, or, where KDIGO was unavailable, a renal Sequential Organ Failure Assessment score of 3 or higher). We contacted the principal investigator of each eligible trial to request individual patient data. From the included trials, any patients without acute kidney injury or who were not randomly allocated were not included in the individual patient data meta-analysis. The primary outcome was all-cause mortality at day 28 after randomisation. This study is registered with PROSPERO (CRD42019125025). Findings: Among the 1031 studies identified, one study that met the eligibility criteria was excluded because the recruitment period was not recent enough, and ten (including 2143 patients) were included in the analysis. Individual patient data were available for nine studies (2083 patients), from which 1879 patients had severe acute kidney injury and were randomly allocated: 946 (50%) to the delayed RRT group and 933 (50%) to the early RRT group. 390 (42%) of 929 patients allocated to the delayed RRT group and who had available data did not receive RRT. The proportion of patients who died by day 28 did not significantly differ between the delayed RRT group (366 [44%] of 837) and the early RRT group (355 [43%] of 827; risk ratio 1·01 [95% CI 0·91 to 1·13], p=0·80), corresponding to an overall risk difference of 0·01 (95% CI −0·04 to 0·06). There was no heterogeneity across studies ( I 2 =0%; τ 2 =0), and most studies had a low risk of bias. Interpretation: The timing of RRT initiation does not affect survival in critically ill patients with severe acute kidney injury in the absence of urgent indications for RRT. Delaying RRT initiation, with close patient monitoring, might lead to a reduced use of RRT, thereby saving health resources. Funding: None.